(untitled) (Pakistan Journal of Science, 2016)
Mass Transit System is considered as one of the important parameter in reducing Public Transport (PT) problem worldwide. Commonly used systems under the umbrella of Mass Transit are Bus Rapid Transit System (BRTS) and Light Rail Transit System (LRTS). BRTS is considered better in urban transport planning because of its lesser construction cost and higher accessibility over LRTS. PT in Lahore is inadequate as compared to actual travel demand. This study / project aims at estimating the choice of informal transport as well as own-vehicle (private vehicle) users and also to identify encouraging factors which facilitate them to shift to BRTS. A Stated Preference (SP) approach was used to collect data about travel time, cost, distance, mode choice along with some socio-economic attributes, such as gender, age and occupation. Binary logistic regression was performed for creation of regression models. It was found that BRTS has a potential to attract motorcycle users. However, car users prefer their own vehicles. Modal shift of people was found dependent on travel time and trip cost.